IMF Research Bulletin, March 2007 - Spilimbergo, Antonio (Washington, D.C. : International Monetary Fund, 2007)
Research summaries on (1) globalization and macroeconomic volatility (by M. Ayhan Kose), and (2) international financial integration and domestic financial systems (by Thierry Tressel); country study on Germany (by Stephan Danninger); book summary of China and India--Learning from Each Other; listing of contents of Vol. 54, Issue No. 1 of IMF Staff Papers; listing of recent external publications by IMF staff; listing of recent IMF Working Papers; and listing of visiting scholars at the IMF during September 2006-April 2007.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet